2014
DOI: 10.1039/c3ra47423b
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective 1,4-addition of kojic acid derivatives to β-nitroolefins catalyzed by a cinchonine derived sugar thiourea

Abstract: A highly enantioselective Michael addition reaction of kojic acid derivatives to b-nitroolefins has been accomplished using a cinchonine derived sugar thiourea. The reaction provides the corresponding Michael adducts in excellent yields with a high degree of enantioselectivity (up to 99% ee) in short reaction time with low catalyst loading. The Michael adducts are found to exhibit promising cytotoxicity against various cancer cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…In recent studies [6,17] carbohydrate thiourea derivatives showed good enantioselectivities in Michael reactions in acetonitrile and dichloromethane. In addition, according to our unpublished results, cinchona thioureas and squaramides obtain excellent chiral induction in Michael reactions in methyl tert-butyl ether (MTBE).…”
Section: Application Of the New Organocatalysts In Asymmetric Michaelmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent studies [6,17] carbohydrate thiourea derivatives showed good enantioselectivities in Michael reactions in acetonitrile and dichloromethane. In addition, according to our unpublished results, cinchona thioureas and squaramides obtain excellent chiral induction in Michael reactions in methyl tert-butyl ether (MTBE).…”
Section: Application Of the New Organocatalysts In Asymmetric Michaelmentioning
confidence: 99%
“…Numerous asymmetric reactions, such as aldol, Mannich, Michael, Henry, amination, Biginelli, cyanosilylation and aza-Morita-BaylisHillman reactions, have been accomplished by these catalysts [3]. Recently, bifunctional thiourea derivatives have been recognized as effective organocatalysts for asymmetric Michael addition reactions [4][5][6]. Therefore, the development of simple and efficient bifunctional thiourea catalysts has great interest.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…at − 10 • C for 4 days to obtain products 89 in 58%-99% yields and good enantioselectivities (Scheme 34). Moreover, Subba Reddy et al 89 reported a similar approach using cinchonine-derived sugar thioureas in 2014, in which the corresponding Michael adducts exhibited promising cytotoxicity against various cancer cell lines.…”
mentioning
confidence: 99%